Holographic gratings recorded in poly(lactic acid)/azo-dye films - Cambiasso, Javier (2015)
Diffraction gratings were recorded in biodegradable polymer films of poly(lactic acid) doped with the photoisomerisable azo-dye (Disperse Orange 3). It is shown that the diffraction efficiency of the recorded grating can be improved by 220% via an all-optical treatment. This all-optical treatment consists of a pre-irradiation of the sample with the writing laser beam at high power during a short period of time, preventing damage of the material, followed by a much longer inscription at relatively low power. Furthermore, it is shown that the addition of a small amount of 0.05 wt% of multi-walled carbon nanotubes to the photoresponsive polymer increases the maximum diffraction efficiency as well as the remanent efficiency by 20%. Finally, this last photoresponsive nano-composite is also sensitive to the pre-irradiation treatment.